2014
DOI: 10.1159/000363695
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Prenatal Stress in Female 5-Htt-Deficient Mice: Towards Molecular Mechanisms of Resilience

Abstract: Prenatal stress (PS) exposure is known to increase the risk of developing emotional disorders like major depression in later life. However, some individuals do not succumb to adversity following developmental stress exposure, a phenomenon referred to as resilience. To date, the molecular mechanisms explaining why some subjects are vulnerable and others more resilient to PS are far from understood. Recently, we have shown that the serotonin transporter (5-HTT) gene may play a modulating role in rendering indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…As discussed earlier, a moderating factor of MS in this regard might have been the maternal response to MS exposure (Own et al, 2013). The molecular basis of this phenomenon of less effect of adverse factors has been investigated in manifold experiments and a number of behavioral, physiological and molecular factors were identified as relevant mediators of individual susceptibility to stress (Jakob et al, 2014; Anacker et al, 2016; Han and Nestler, 2017). As one important factor of individual stress susceptibility epigenetic modifications such as DNA methylation have been identified (Dudley et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, a moderating factor of MS in this regard might have been the maternal response to MS exposure (Own et al, 2013). The molecular basis of this phenomenon of less effect of adverse factors has been investigated in manifold experiments and a number of behavioral, physiological and molecular factors were identified as relevant mediators of individual susceptibility to stress (Jakob et al, 2014; Anacker et al, 2016; Han and Nestler, 2017). As one important factor of individual stress susceptibility epigenetic modifications such as DNA methylation have been identified (Dudley et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Elements known for their modulatory function of the HPA axis include the glucocorticoid receptor (GR; Nr3c1 ) 17 , 28 , corticotropin releasing hormone receptor 1 ( Crhr1 ) 29 , 30 , and brain-derived neurotrophic factor ( Bdnf ) 31 , 32 . Furthermore, growth hormone ( Gh ) and myelin basic protein ( Mbp ) appeared as candidate genes in previous studies 33 35 . Both play important roles in the brain as they are involved in neural processes such as myelination.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, it has been reported that male PS Sprague-Dawley rats displayed vulnerability in the FST (van den Hove et al, 2013). Other studies performed with mice have also demonstrated contrasting behavioral, gender-specific responses in the FST as a result of prenatal stress (Jakob et al, 2014;van den Hove et al, 2011).…”
Section: Discussionmentioning
confidence: 97%